Molecularly Responsive Aptamer-Functionalized Hydrogel for Continuous Plasmonic Biomonitoring - Park, Soohyun; Gerber, Alice; Santa, Cátia; Aktug, Gizem; Hengerer, Bastian; Clark, Heather A; Jonas, Ulrich; Dostalek, Jakub; Sergelen, Khulan (Journal of the American Chemical Society, 2025)
Continuous in vivo monitoring of small molecule biomarkers requires biosensors with reversibility, sensitivity in physiologically relevant ranges, and biological stability. Leveraging the real-time, label-free detection capability of surface plasmon resonance (SPR) technology, a molecularly responsive hydrogel film is introduced to enhance small molecule sensitivity. This advanced biosensing platform utilizes split-aptamer-cross-linked hydrogels (aptagels) engineered using 8-arm poly(ethylene glycol) macromers, capable of directly and reversibly detecting vancomycin. Investigation through SPR and optical waveguide mode, along with quartz crystal microbalance with dissipation (QCM-D) monitoring, reveals that the reversible formation of analyte-induced ternary molecular complexes leads to aptagel contraction and significant refractive index changes. Optimization of aptamer cross-link distribution and complementarity of split-aptamer pairs maximizes conformational changes of the aptagel, demonstrating a detection limit of 160-250 nM for vancomycin (6-9 fold improvement over monolayer counterpart) with a broad linear sensing range up to 1 mM. The aptagel maintains stability over 24 h in blood serum and 5 weeks in diluted blood plasma (mimicking interstitial fluid). This structurally responsive aptagel platform with superior stability and sensitivity offers promising avenues for continuous in vivo monitoring of small molecules.
Keywords: vankomycin; mikrorovnovážné techniky křemenného krystalu; Surface Plasmon Resonance; povrchová plasmonová rezonance; biosenzitivní techniky; Hydrogels; Biosensing Techniques; Aptamers, Nucleotide; lidé; Polyethylene Glycols; Humans; Vancomycin; Quartz Crystal Microbalance Techniques; aptamery nukleotidové; polyethylenglykoly; hydrogely